Efektifitas Model Problem Based Learning dengan Media Wordwall guna Meningkatkan Hasil Belajar Siswa - Siti Kholifah; Heni Purwanti; Noer Hudha Ekowati; Ali Shodiqin (Departement of Mathematics Education, 2024)
The results of the mathematics test show that students have not reached the optimal level and are still below the planned benchmarks. Therefore, there needs to be improvement. The learning outcomes are poor because students still have difficulty understanding the correct use of formulas. Wordwall media can increase student understanding and make it easier for teachers and students to convey information because it is available. This research is quantitative research where this research uses a post-test only experimental design approach. This research population involved all class XI students at SMA Negeri 14 Semarang in the 2023/2024 academic year. There are two classes used, where class XI-3 is the experimental class and class XI-4 is the control class. The results obtained are that both data are normally distributed and homogeneous. After carrying out the independent sample t-test, the data obtained was that H0 was rejected so that there was a significant difference between the experimental class and the control class. The experimental class that was given treatment using the PBL model and Wordwall media got better learning outcomes than the control class that was not given treatment. The research results showed that Wordwall learning media influenced mathematics students' learning outcomes. This is shown by the fact that students in the experimental class XI-3 learned mathematics better than students in the control class XI-4. Therefore, it can be concluded that, compared to not using Problem based learning media with Wordwall media, there is an influence on mathematics student learning outcomes.